2014
DOI: 10.1016/j.combustflame.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gas-phase and in-depth radiation absorption on ignition and steady burning rate of PMMA

Abstract: Article:Staggs, J (2014) The effects of gas-phase and in-depth radiation absorption on ignition and steady burning rate of PMMA. Combustion and Flame, 161 (12 ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Some previous studies considered incident radiative heat flux only at the surface [14], and converted it to the heat fluxes into the solid phase. While some other studies suggested that in-depth radiation causes ignition delay [44,45]. The authors believe it should be taken into account.…”
Section: Radiation Model and Estimation Of Mean Beam Lengthmentioning
confidence: 80%
See 1 more Smart Citation
“…Some previous studies considered incident radiative heat flux only at the surface [14], and converted it to the heat fluxes into the solid phase. While some other studies suggested that in-depth radiation causes ignition delay [44,45]. The authors believe it should be taken into account.…”
Section: Radiation Model and Estimation Of Mean Beam Lengthmentioning
confidence: 80%
“…It would be outside the scope of the present study to resolve these issues, which can be revisited later when such information/data is available. In the present study, only absorption was accounted for by Beer's law [3,44,45] and radiative emissivity inside the PMMA was neglected. The heat flux of in-depth radiation q dep due to absorption can be written as below using Beer's law :…”
Section: Radiation Model and Estimation Of Mean Beam Lengthmentioning
confidence: 99%
“…Additionally, Staggs [ 27 ] proposed the following formulation to qualitatively estimate the effects of in-depth absorption on ignition: which indicates that will reduce in direct proportion to .…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Moreover, it was also found that in-depth absorption exists even for the presence of coated carbon black on the surface. Bal [ 19 ] and Staggs [ 27 ] numerically investigated the ignition behaviors of PMMA considering both surface and in-depth absorption, and an optimized combination was suggested. Also, it was found that the traditional coating of black carbon added on the sample does not cancel in-depth radiation absorption but rather its effect is to absorb around 35% of the incoming radiation at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Recent contributions on ignition at high incident heat flux [ 18 , 19 ], have shown that for infra-red heat sources the ignition time—heat flux dependence predicted by Equation (8) above is reliable only for moderate heat fluxes up to ~40 kWm −2 , particularly for PMMA. At higher heat flux, it appears that infra-red absorptivity has a significant effect on ignition time and that observed ignition resistance is actually greater than that predicted by the simple theory above.…”
Section: Thermal Insulationmentioning
confidence: 99%